What are you doing with your life? : teen books on living series - Krishnamurti, J. (Chennai : Krishnamurti Foundation India, 2006)
WHAT ARE YOU DOING WITH YOUR LIFE?J. KRISHNAMURTII TEACHINGS FOR TEENS, edited by Dale Carlson. Teens learn to understand the self, the purpose of life, work, education, relationships. Through paying attention rather than accepting the authority of their conditioning, they can find out for themselves about love, sex, marriage, work, education, the meaning of life and how to change themselves and the world. The Dalai Lama calls Krishnamurti "One of the greatest thinkers of the age."
Includes index.
Keywords: Philosophy; Teenagers -- Religious life; Teenagers -- Conduct of life